2009
DOI: 10.1128/jcm.00418-07
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Comparison of Eubacterial PCR and Measurement of Procalcitonin Levels with Blood Culture for Diagnosing Septicemia in Intensive Care Unit Patients

Abstract: Rapid identification of infection has a major impact on the clinical course, management, and outcome of critically ill intensive care unit (ICU) patients. We compared the results of PCR and procalcitonin with blood culture for ICU patients suspected of having septicemia. Ninety patients (60 patients meeting the criteria for sepsis and 30 patients not meeting the criteria for sepsis) were evaluated. Compared with blood culture as the gold standard, the sensitivity, specificity, and positive and negative predict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
15
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 29 publications
2
15
0
1
Order By: Relevance
“…30,32 In contrast to this, majority of studies have reported that procalcitonin was a better marker to estimate the severity, prognosis, or further course of the sepsis. 33,36 This study was consistent to the others with a few minor limitations. First, serial PCT monitoring every day was avoided which may improve its performance as an aid for follow up of sepsis.…”
supporting
confidence: 74%
“…30,32 In contrast to this, majority of studies have reported that procalcitonin was a better marker to estimate the severity, prognosis, or further course of the sepsis. 33,36 This study was consistent to the others with a few minor limitations. First, serial PCT monitoring every day was avoided which may improve its performance as an aid for follow up of sepsis.…”
supporting
confidence: 74%
“…Homemade multiplex or broad-range PCR assays for the detection of bloodstream pathogens in cases of sepsis or febrile neutropenia have provided variable sensitivity and specificity compared with blood cultures (5,8,9,28,31,42,44). Their use is limited by the lack of standardized technical procedures and commercially available systems.…”
mentioning
confidence: 99%
“…Early and reliable diagnosis for appropriate treatment is essential for improving the prognosis of infected patients. While so far, no single biomarker was able to replace time-consuming blood cultures, some, like procalcitonin (PCT), C-reactive protein (CRP), and interleukin-6 (IL-6), are commonly used for additional assessments (2,3).…”
mentioning
confidence: 99%